Comparison of Ethanol Extract from Roots, Leaves, and Flowers of Calotropis gigantea as Anticancer on T47D Breast Cancer Cell Lines - Mutiah, Roihatul; Sukardiman, Sukardiman; Widyawaruyanti, Aty; Zulaikah, Siti (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2016)
This research aims to find out the anticancer activity of ethanol extract from the roots, leaves, and flowers of Calotropis gigantea. This experiment was conducted by MTT method on T47D breast cancer cell line. The result showed that the root of Calotropis gigantea was more cytotoxic (IC50 89.76 Î¼g/mL) on T47D breast cancer cell line than the leaves (IC50 459.51 Î¼g/mL) and the flowers (IC501000). Based on the result, roots are potent to be chemotherapeutic agent, especially in breast cancer.